2011
DOI: 10.4269/ajtmh.2011.11-0333
|View full text |Cite
|
Sign up to set email alerts
|

Seventeen Years of Annual Distribution of Ivermectin Has Not Interrupted Onchocerciasis Transmission in North Region, Cameroon

Abstract: We studied onchocerciasis transmission and impact on ocular morbidity in three health districts in North Region, Cameroon, where annual mass ivermectin treatment has been provided for 12–17 years. The studies, which took place from 2008 to 2010, consisted of skin snips for microfilariae (mf), palpation examinations for nodules, slit lamp examinations for mf in the eye, and Simulium vector dissections for larval infection rates. Adults had mf and nodule rates of 4.8% and 13.5%, respectively, and 5.5% had mf in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 28 publications
(37 reference statements)
5
75
0
Order By: Relevance
“…These findings are consistent with those findings obtained from northern Cameroon, which showed that 17 years of annual mass treatment did result in a significant decrease of skin mf and nodules but did not interrupt transmission. 11 When contrasted with recently published studies from Senegal, Mali, and Nigeria, which show successful interruption of transmission after annual ivermectin treatment, this study points out the importance of local variations in the ecology of transmission of onchocerciasis in determining the ultimate success of an elimination program. 11 Local variations in vector density, biting rate, and vector capacity will all affect the potential for the success of an elimination program and by extension, the strategic plan adopted by the program to interrupt transmission.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…These findings are consistent with those findings obtained from northern Cameroon, which showed that 17 years of annual mass treatment did result in a significant decrease of skin mf and nodules but did not interrupt transmission. 11 When contrasted with recently published studies from Senegal, Mali, and Nigeria, which show successful interruption of transmission after annual ivermectin treatment, this study points out the importance of local variations in the ecology of transmission of onchocerciasis in determining the ultimate success of an elimination program. 11 Local variations in vector density, biting rate, and vector capacity will all affect the potential for the success of an elimination program and by extension, the strategic plan adopted by the program to interrupt transmission.…”
Section: Discussionmentioning
confidence: 50%
“…It is possible that the amount of time necessary to eliminate transmission could vary considerably among foci in Africa depending on the initial prevalence of infection and the intensity of transmission. 11 Epidemiological assessments done in 1993 had shown that the Nyagak-Bondo area of northwestern Uganda (Zombo district and parts of Arua and Nebbi districts) was endemic for onchocerciasis. The vectors in Nyagak-Bondo focus are members of the S. neavei complex, with larvae and pupae that live in a phoretic association on freshwater crabs of species Potamonautes aloysiisabaudiae and P. niloticus.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of ivermectin treatments is also a factor. Indeed some failures of annual distributions to interrupt transmission [90,93,94,95] have led to the adoption by many health authorities of biannual treatments which have been shown to improve the efficacy of ivermectin, except in the case of sub-optimally responding parasites [96].…”
Section: Microfilaricidesmentioning
confidence: 99%
“…PZQ, administered at the standard single dose of 40 mg kg 21 , is the only currently available drug for schistosomiasis. PZQ is also efficacious against several of the food-borne trematodes, administered at single doses of between 25 and 50 mg kg 21 .…”
Section: Introductionmentioning
confidence: 99%